Pengaruh Variasi Dosis Koagulan Alami Serbuk Biji Mengkudu (Morinda Citrifolia L) terhadap Kekeruhan Air Sungai - Hadianor Hadianor; Abdul Khair; Syarifudin A (HB PRESS, 2025)
Turbidity is one of the important parameters in determining the quality of clean water. The river water used by the people of Desa Melayu Tengah as a source of daily needs has a turbidity level that exceeds the standard quality threshold. This study aims to determine the effect of varying doses of the natural coagulant from noni seed powder (Morinda citrifolia L.) on the reduction of river water turbidity. This study uses the true experimental method with a post-test only with control group design. Water samples were taken from the Martapura River, then treated with varying coagulant doses of 0 mg/L, 25 mg/L, 50 mg/L, and 75 mg/L, each with 6 repetitions. Data analysis was conducted using the one-way ANOVA test followed by the LSD (least significant difference) test. The research results showed a significant difference between the treatment groups (p < 0.001), with the optimum dose at 25 mg/L. However, the turbidity value after treatment has not yet reached the quality standard (< 3 NTU) based on Permenkes No. 2 of 2023. The use of this material still requires further development, including in terms of extraction methods, the correct dosage, and the possibility of combining it with other more reactive coagulant materials. For the time being, the public is still advised to use proven effective water purification methods, such as simple filtration, sedimentation with alum, or household filtration systems based on sand and activated charcoal.